THE IMPACT OF SOCIO-ECONOMIC FACTORS OF HORTICULTURAL FARMERS ON ACCESS TO MICROFINANCE IN EAST JAVA - Hasbiy, Khoirul Umam; Hardana, Andrean Eka (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Almost all corporate financing in the agriculture sector is dependent on interest. Because the features of the agricultural sector are incompatible with the finance sector, banks often show little interest in funding the agricultural sector. The purpose of this study were Analyze the socio-economics factors that influence the decision of horticultural farmers in East Java in accessing microfinance. The method of determining the location of the research was carried out in two locations, namely Wonomulyo Village, Poncokusumo Subdistrict, Malang Regency, dan Pacet Village, Pacet Subdistrict, Mojokerto Regency. 160 farmers were chosen as the study's sample size using the proportionate stratified sampling technique and the Slovin formula. To answer these problems descriptive analysis, logistic regression analysis (logit) was used. Formal institutions assigned to channel the funds include government banks and private banks. Informal institutions that carry out the distribution of micro-credit funds are the private sector or institutions from the farmers themselves. The majority of farmers generally know that the level of formal financing sources is indeed lower, but administrative procedures are considered difficult. Based on the results of logistic regression analysis for the factors that influence the decisions of Horiculture farmers in East Java in accessing credit, including education, length of business, land area, and income. It is recommended that in order to formulate steps for the ease of taking out agricultural loan, Field Extension Officers, regional cooperatives, government banks, and private banks should conduct specific studies and take specific approaches.